2011
DOI: 10.1002/hbm.21379
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between regional and inter‐regional functional connectivity deficits in schizophrenia

Abstract: While schizophrenia is frequently characterized as a disorder of disturbed functional connectivity, the causes and pathophysiological origins of such disturbances remain unclear. The aim of this study was to better elucidate the mechanistic causes of abnormal functional connectivity in schizophrenia, measured as the extent of temporal correlation between endogenous fluctuations recorded at anatomically discrete brain regions during resting-state functional MRI. An approach was developed to perform whole-brain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
107
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(118 citation statements)
references
References 66 publications
9
107
2
Order By: Relevance
“…In conjunction with previous studies [10][11][12][13] , our results indicate the PreCG has abnormal connectivity with brain regions like Thalamus and Hippocampus, but these impairments are not similar in two hemispheres. We also analyzed the functional connectivity differences between male and female patients with schizophrenia and showed the regions like Thalamus are more affected in the female patients with schizophrenia.…”
Section: Introductionsupporting
confidence: 87%
“…In conjunction with previous studies [10][11][12][13] , our results indicate the PreCG has abnormal connectivity with brain regions like Thalamus and Hippocampus, but these impairments are not similar in two hemispheres. We also analyzed the functional connectivity differences between male and female patients with schizophrenia and showed the regions like Thalamus are more affected in the female patients with schizophrenia.…”
Section: Introductionsupporting
confidence: 87%
“…Investigators have observed a direct relationship between spiking output during neural firing and phase locking across nodes, thus resulting in higher measured connectivity/coherence (Chawla et al, 1999(Chawla et al, , 2000. These latest findings offer evidence that the increased connectivity observed in the literature summarized here There is also evidence that measured changes in functional connectivity between ROIs in clinical samples may be a consequence not only of altered coupling between regions but also of increased heterogeneity in the signals within each ROI (Bassett et al, 2011;Zalesky et al, 2012). In schizophrenia, decreased pairwise regional functional connectivity has been found to strongly correlate with loss of intraregional homogeneity, increased variance, and decreased signal power (Bassett et al, 2011;Zalesky et al, 2012).…”
Section: Connectivity Frequencies For All Studies I Hypermentioning
confidence: 55%
“…Tzourio-Mazoyer et al defined a neurobiologically-informed cortical parcellation based on regions of interest that are known to house specific functional areas in the brain [11]. By contrast, Zalesky et al [12] proposed a more exhaustive approach that treats each voxel as its own ROI, resulting in tens of thousands of ROIs on the cortex. An intermediate approach proposed by Wig [13] treats the elements of random parcellations of the cortex as nodes, but this approach may still fail to capture the borders of regions that make sense for capturing pathways.…”
Section: Introductionmentioning
confidence: 99%